UNLOCKING THE SECRETS TO PERFECT WORD ARTICULATION - Aliboeva Nilufar Makhamatali kizi; Adolatxon Shermuhammedova Ahadjon kizi (International Journal on Integrated Education, 2023)
In this article, we are going to inform you about how to pronounce of the English words perfectly. It is common that we must pronounce the words in any language correctly to natives. Here, you can learn about the secrets of them.